2017
DOI: 10.7287/peerj.preprints.3250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enumerating common molecular substructures

Abstract: Finding and enumerating common molecular substructures is an important task in cheminformatics, where small molecules are often modeled as molecular graphs. We introduce the problem of enumerating all maximal k-common molecular fragments of a pair of molecular graphs. A k-common fragment is a common connected induced subgraph that consists of a common core and a common k-neighborhood. It is thus a generalization of the NP-hard task to enumerate all maximal common connected induced subgraphs (MCCIS) of two grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It can be shown that the k-MCF-E problem is a generalisation of enumerating all maximal CCIS (MCCIS-E). 132 Note that there is a fundamental difference between enumerating all maximal CCIS (MCCIS-E) and the well-known problem of finding the maximum (largest) CCIS, for which many exact algorithms and heuristics have been proposed, especially in the context of molecular graphs. [133][134][135] For this application, we adapted the MCCIS-E algorithm of Koch 136 to k-MCF-E.…”
Section: Molecules and Graph Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that the k-MCF-E problem is a generalisation of enumerating all maximal CCIS (MCCIS-E). 132 Note that there is a fundamental difference between enumerating all maximal CCIS (MCCIS-E) and the well-known problem of finding the maximum (largest) CCIS, for which many exact algorithms and heuristics have been proposed, especially in the context of molecular graphs. [133][134][135] For this application, we adapted the MCCIS-E algorithm of Koch 136 to k-MCF-E.…”
Section: Molecules and Graph Matchingmentioning
confidence: 99%
“…[133][134][135] For this application, we adapted the MCCIS-E algorithm of Koch 136 to k-MCF-E. When combined with additional data reduction techniques, we showed that our algorithm for k-MCF-E for k > 0 is highly efficient even for large molecular graphs, 132 allowing databases containing 100,000s of drug-like molecules to be routinely screened.…”
Section: Molecules and Graph Matchingmentioning
confidence: 99%